Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

De- and Reterritorializing Identities: The Global Hip Hop Nation at Work in a Youth Hip Hop Recording Studio - Laniel-Tremblay, Édouard; Low, Bronwen (Critical Approaches Toward a Cosmopolitan Education, 2022)
This essay builds on previous studies of the “translanguaging” practices of members of the Montreal Hip Hop community (Low & Sarkar, 2014; Sarkar & Low, 2012) to explore how the challenge to linguistic norms in Quebec is also a challenge to social and identity norms. Our analysis is based on interviews with young musicians attending a community recording studio program in Montreal, the studio’s social media presence, and a track created in collaboration with youth in Paris. Through their relationships in the studio as well as their music, the youth de- and reterritorialize their identities (Papastergiadis, 2000), mobilizing local and global Hip Hop cultural references and communities in ways that challenge dominant narratives of belonging in Quebec and Canada.

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)